PEMANFAATAN TANAH TERLANTAR BERDASARKAN PERMEN AGRARIA DAN TATA RUANG / KEPALA BADAN PERTANAHAN NASIONAL NO. 20 TAHUN 2021 - Laili Saiful, Wardatul Muniroh; Fathullah, Kholidazia Elhamzah (STIH Zainul Hasan Kraksaan Kraksaan, 2024)
Abstract Land is a gift from god almighty which is one of the main elements in all activities of human life. Criteria for abandoned land and utilization procedures according to Minister of ATR/Head of BPN Regulation No. 20 of 2021 concerning Procedures for Controlling and Utilizing Abandoned Areas and Land. The aim of this research is to analyze the regulation of abandoned land in laws and regulations in the land sector and to discuss the criteria for determining whether land is declared as abandoned land with the issuance of PP Number 20 of 2021 concerning Controlling Abandoned Areas and Land. This research is normative legal research which uses legal materials with a statutory approach and a contextual approach. The source of the legal material for this research comes from primary legal material which is Ministerial Regulation Number 20 of 2021. The results of this research found that Ministerial Regulation Number 20 of 2021 states that abandoned land is entitled land, land with management rights, and land obtained based on the basis of land control. which are intentionally not cultivated, not used, not exploited, and/or not maintained. Therefore, land abandonment must be prevented and regulated to reduce or eliminate its negative impacts. Thus, preventing, controlling and utilizing abandoned land is an important step and prerequisite for carrying out national development programs, especially in the agrarian sector which has been mandated by the 1945 Constitution of the Republic of Indonesia, Basic Regulations on Agrarian Principles. Keyword : Utilization, Abandoned Land, Ministerial Regulations, Control and Utilization of Abandoned Land.